External Capital Factors and Increasing Returns in U.S. Manufacturing - Morrison, Catherine J.; Siegel, Donald (The Review of Economics and Statistics, 1997)
Theoretical models of endogenous growth identify capital accumulation and returns as a potential stimulus to economic growth. Existing empirical studies, however, are based on a limited notion of these returns, which follows from the simple production function framework used for estimation. The purpose of this study is to examine growth issues using dynamic cost function estimation. This methodology enables us to broaden the concept of returns to include returns arising from short-run quasi-fixity of private capital, long-run (internal) scale economies, and external “knowledge” factors—overall investment in research (R&D), technology (high-tech capital), and education (human capital). Based on detailed industry-level data, we find evidence of increasing returns to scale arising from cost savings on variable inputs, although diminishing returns to capital are prevalent. Our results also show that knowledge factors augment growth. More importantly, they appear to explain a substantial proportion of measured scale economies.